PENGARUH BIMBINGAN STRATEGI COPING RELIGIUS GURU DAN POLA ASUH ORANG TUA TERHADAP PERILAKU PROSOSIAL SISWA DI ERA MODERN - Saimun Saimun; Hanafi Hanafi (Consilium: Education and Counseling Journal, 2026)
Developments in the modern era, characterised by the rapid flow of digital information, have led to changes in students’ social behaviour. This study aims to empirically analyse the influence of teachers’ guidance on religious coping strategies and parental rearing styles on students’ prosocial behaviour. The method used was quantitative with a survey approach, employing a Likert scale questionnaire (1–5) distributed to 69 students in Years 10 and 11 at State Senior High School 8 Mataram via random sampling. The data were analysed using descriptive and inferential statistics with the aid of IBM SPSS software, including normality tests, t-tests, F-tests, and the coefficient of determination (R²). The results of the study indicate that teachers’ guidance on religious coping strategies (X1) and parental upbringing (X2) have a significant effect on students’ prosocial behaviour (Y) with a significance value of 0.000 < 0.05. Variable X1 contributes 22.8%, whilst X2 contributes 23.8%, both falling within the moderate influence category. The implications of this study emphasise the importance of synergy between the roles of teachers and parents in providing guidance grounded in religious values to foster students’ prosocial behaviour and minimise negative influences in the modern era.